Voces de mujeres en la Edad Media - Corral Díaz, Esther (2018)
The contributions gathered in this volume take a fresh look at the medieval history of women. From powerful nobility as a cultural actor, to prominent and lesser-known female writers, including female protagonists of lyric poetry and narrative literature, the book offers interdisciplinary perspectives on historical, authorial, and textual femininity.